Modelamiento de la Distribución Espacial de Nutrientes en un Agro Ecosistema ubicado en el Cantón Patate Provincia de Tungurahua. - Acosta Panimboza, Rovinson Santiago (2019)
The spatial and temporal variability of the nutrients are given by the parental material from which the soil was formed, the particular conditions of formation, management and variation among the seasons of the year. The modeling of the spatial distribution of nutrients was developed in an agroecosystem located in the Patate canton, Tungurahua province, with an area of 20336.48m2. A 40m * 40m sampling grid was applied, with 16 sampling points systematically located equidistantly. The potential of hydrogen (pH), organic matter (OM), nitrogen (N), phosphorus (P), potassium (K) and electrical conductivity (CE) was determined. To these parameters, dispersion measures were calculated. Through a geostatistical analysis, the spatial structure of the variables was established to fit an experimental semivariogram, spherical, exponential and nugget effect. The results and their behavior were represented in georeferenced maps. With the kriging interpolation method, the zones with low, medium and high contents of the nutrients were determined. Optimal K levels were found with values between 0.8cmol/kg and 1.49cmol/kg for the entire study area, exceeding the optimal level of > 0.4cmol/kg. For P, a concentration between 27.4mg/kg and 68.8mg/kg was found that exceeds the high range of > 21mg/kg. The area has a non-saline soil (max CE = 1.89dS/m). It was established that the limiting nutrient was N with values between 0.7% and 0.3%, all deficient. The MO also showed low and medium values in 61.76% of the area. To compensate these deficits, 2553 Kg of fresh organic material are needed, while the N deficit would be compensated by processes of MO mineralization and nitrogen fixation with a combination of crops with alfalfa (Medicago sativa).